17(R)‐resolvin D1 ameliorates bleomycin‐induced pulmonary fibrosis in mice. Issue 12 (10th December 2015) - Yatomi, Masakiyo; Hisada, Takeshi; Ishizuka, Tamotsu; Koga, Yasuhiko; Ono, Akihiro; Kamide, Yosuke; Seki, Kaori; Aoki‐Saito, Haruka; Tsurumaki, Hiroaki; Sunaga, Noriaki; Kaira, Kyoichi; Dobashi, Kunio; et al.
Abstract: Idiopathic pulmonary fibrosis (IPF) is a destructive inflammatory disease with limited therapeutic options. Inflammation plays an integral role in the development of pulmonary fibrosis. Unresolved inflammatory responses can lead to substantial tissue injury, chronic inflammation, and fibrosis. The resolvins are a family of endogenous ω ‐3 fatty acid derived‐lipid mediators of inflammation resolution. Resolvin D1 (RvD1) displays potent anti‐inflammatory, pro‐resolving activity, without causing immunosuppression. Its epimer, 17(R)‐resolvin D1 (17(R)‐RvD1), exhibits equivalent functionality to RvD1. In addition, 17(R)‐RvD1 is resistant to rapid inactivation by eicosanoid oxidoreductases. In the present study, we tested the hypothesis that 17(R)‐RvD1 can provide a therapeutic benefit in IPF by reducing inflammation and pulmonary fibrosis, while leaving the normal immune response intact. Mice were exposed to bleomycin (BLM) via micro‐osmotic pump to induce pulmonary fibrosis, and were then treated with 17(R)‐RvD1 or vehicle by intraperitoneal injection. Administration of 17(R)‐RvD1 from the start of BLM treatment attenuated neutrophil alveolar infiltration, lung collagen content, and Interleukin‐1 β (IL‐1 β ), transforming growth factor‐ β 1 (TGF‐ β 1), connective tissue growth factor (CTGF), and type I collagen mRNA expression, along with subsequent reduction in histologically detectable fibrosis. The 17(R)‐RvD1‐induced infiltration of inflammatory cells was inhibited by an antagonist of lipoxin A4 receptor/formyl peptide receptor 2 (ALX/FPR2). The administration of 17(R)‐RvD1 at the later fibrotic stage also improved the lung failure. These results suggest that 17(R)‐RvD1 attenuates pulmonary fibrosis by promoting the resolution of neutrophilic inflammation and also provides pulmonary restoration. These data highlight the therapeutic potential of 17(R)‐RvD1 in the management of this intractable disease. Abstract : Administration of 17(R)‐RvD1 from the start of BLM treatment attenuated neutrophil alveolar infiltration, lung collagen content, and Interleukin‐1 β (IL‐1 β ), transforming growth factor‐ β 1 (TGF‐ β 1), connective tissue growth factor (CTGF) and type I collagen mRNA expression, along with subsequent reduction in histologically detectable fibrosis. The administration of 17(R)‐RvD1 at the later fibrotic stage also improved the lung failure. These results suggest that 17(R)‐RvD1 attenuates pulmonary fibrosis by promoting the resolution of neutrophilic inflammation and also provides pulmonary restoration.